M2 occlusions as targets for endovascular therapy: comprehensive analysis of diffusion/perfusion MRI, angiography, and clinical outcomes. (12th May 2014) - Sheth, Sunil A; Yoo, Bryan; Saver, Jeffrey L; Starkman, Sidney; Ali, Latisha K; Kim, Doojin; Gonzalez, Nestor R; Jahan, Reza; Tateshima, Satoshi; Duckwiler, Gary; Vinuela, Fernando; Liebeskind, David S
Abstract : Background: The ideal population of patients for endovascular therapy (ET) in acute ischemic stroke remains undefined. Recent ET trials have moved towards selecting patients with proximal middle cerebral artery (MCA) or internal carotid artery occlusions, which will likely leave a gap in our understanding of the treatment outcomes of M2 occlusions. Objective and methods: To examine the presentation, treatment, and outcomes of M2 compared with M1 MCA occlusions in patients undergoing ET by assessing comprehensive MRI, angiography, and clinical data. Results: We found that M2 occlusions can lead to massive strokes defined by hypoperfused and infarcted volumes as well as death or moderate to severe disability in nearly 50% of patients at discharge. Compared with M1 occlusions, M2 occlusions achieved similar Thrombolysis in Cerebral Infarction (TICI) 2b/3 recanalization rates, with significantly less hemorrhage. M2 occlusions presented with smaller infarct and hypoperfused volumes and had smaller final infarct volumes regardless of recanalization. TICI 2b/3 recanalization of M2 occlusions was associated with smaller infarct volumes compared with TICI 0–2a recanalization, as well as less infarct expansion, in patients who received IV tissue plasminogen activator as well as those that did not. Successful reperfusion of M2 occlusions was associated with improved discharge modified Rankin scale. Conclusions: If suitable as targets of ET, M2 occlusions should be given the same consideration as M1 occlusions.